A tribute to Wartenberg’s refined neurological examination - Maranhão, Péricles, Filho; Gonik, Renato (Arquivos de Neuro-Psiquiatria, 2016)
Robert Wartenberg was a renowned 20th century neurologist who contributed greatly to our understanding of the neurological examination. This article aims to illustrate his legacy by highlighting five seminal neurological signs.
Keywords: Robert Wartenberg; neurologic examination